A fully phased octoploid strawberry genome reveals the evolutionary dynamism of centromeric satellites - Xin Jin; Haiyuan Du; Maoxian Chen; Xu Zheng; Yiying He; Andan Zhu (Genome Biology)
Abstract We systematically examine the application of different phasing strategies to decrypt strawberry genome organization and produce a fully phased and accurate reference genome for Fragaria x ananassa cv. “EA78” (2n = 8x = 56). We identify 147 bp canonical centromeric repeats across 50 strawberry chromosomes and uncover the formation of six neocentromeres through centromere turnover. Our findings indicate strawberry genomes have diverged centromeric satellite arrays among chromosomes, particularly across homoeologs, while maintaining high sequence similarity between homologs. We trace the evolutionary dynamics of centromeric repeats and find substantial centromere size expansion in wild and cultivated octoploids compared to the diploid ancestor, F. vesca.